2010
DOI: 10.1007/s11033-010-0150-y
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiles of glutathione S-transferase genes in larval midgut of Bombyx mori exposed to insect hormones

Abstract: Glutathione S-transferases (GSTs) are believed to play a role in the detoxification of xenobiotics, resistance to insect viruses and pesticides, intracellular transport, biosynthesis of hormones and protection against oxidative stress. In this study, we used quantitative real time RT-PCR to examine expression profiles of the silkworm Bombyx mori GST-Sigma (BmGSTS2) and GST-Delta (BmGSTD2) genes in the larval midgut of the silkworm after exposure to 2-hydroxyecdysone (20E) and juvenile hormone analog (JHA). In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…Genetic, biochemical and physiological studies have established the importance of ecdysone signaling in the regulation of metabolic processes. There is an accumulating body of evidence that the expression of specific GSTs can be regulated by 20E and juvenile hormone titers and it has recently been suggested that there are ecdysone binding motifs in the promoter sequence of several GSTs in Bombyx mori [7]. Taken together, our data suggest that the GST16 protein might have an important but yet unknown function in insects with the isomerization (inactivation) of cis-OPDA being one of the catalytic functions attached to it.…”
Section: Direction Of Regulationsupporting
confidence: 55%
“…Genetic, biochemical and physiological studies have established the importance of ecdysone signaling in the regulation of metabolic processes. There is an accumulating body of evidence that the expression of specific GSTs can be regulated by 20E and juvenile hormone titers and it has recently been suggested that there are ecdysone binding motifs in the promoter sequence of several GSTs in Bombyx mori [7]. Taken together, our data suggest that the GST16 protein might have an important but yet unknown function in insects with the isomerization (inactivation) of cis-OPDA being one of the catalytic functions attached to it.…”
Section: Direction Of Regulationsupporting
confidence: 55%
“…Although JH‐responsive genes involving acute toxicity in daphnids have not been reported, a few JH‐responsive genes encoding serine protease and glutathione‐ S ‐transferase have already been identified in insects (Horst et al ., ; Zou et al ., ). Expression of most of glutathione‐ S ‐transferase gene was not fluctuated by JH analogs.…”
Section: Resultsmentioning
confidence: 97%
“…In insects, the expression of GST genes is life-, stage-, sex- and tissue-specific and influenced by internal and external factors including physiological condition, diet and exposure to toxins [21][23]. In N. lugens , GST gene expression levels were generally highest in macropterous adults, but lower in eggs and lower still in nymphs.…”
Section: Resultsmentioning
confidence: 99%